Climatic versus halokinetic control on sedimentation in a dryland fluvial succession. Issue 2 (24th August 2013) - Banham, Steven G.; Mountney, Nigel P.; Marzo, Mariano
Abstract Fluvial systems and their preserved stratigraphic expression as the fill of evolving basins are controlled by multiple factors, which can vary both spatially and temporally, including prevailing climate, sediment provenance, localized changes in the rates of creation and infill of accommodation in response to subsidence, and diversion by surface topographic features. In basins that develop in response to halokinesis, mobilized salt tends to be displaced by sediment loading to create a series of rapidly subsiding mini‐basins, each separated by growing salt walls. The style and pattern of fluvial sedimentation governs the rate at which accommodation becomes filled, whereas the rate of growth of basin‐bounding salt walls governs whether an emergent surface topography will develop that has the potential to divert and modify fluvial drainage pathways and thereby dictate the resultant fluvial stratigraphic architecture. Discerning the relative roles played by halokinesis and other factors, such as climate‐driven variations in the rate and style of sediment supply, is far from straightforward. Diverse stratigraphic architectures present in temporally equivalent, neighbouring salt‐walled mini‐basins demonstrate the effectiveness of topographically elevated salt walls as agents that partition and guide fluvial pathways, and thereby control the loci of accumulation of fluvial successions in evolving mini‐basins: drainage pathways can be focused into a single mini‐basin to preserve a sand‐prone fill style, whilst leaving adjoining basins relatively sand‐starved. By contrast, over the evolutionary history of a suite of salt‐walled mini‐basins, region‐wide changes in fluvial style can be shown to have been driven by changes in palaeoclimate and sediment‐delivery style. The Triassic Moenkopi Formation of the south‐western USA represents the preserved expression of a dryland fluvial system that accumulated across a broad, low‐relief alluvial plain, in a regressive continental to paralic setting. Within south‐eastern Utah, the Moenkopi Formation accumulated in a series of actively subsiding salt‐walled mini‐basins, ongoing evolution of which exerted a significant control on the style of drainage and resultant pattern of stratigraphic accumulation. Drainage pathways developed axial (parallel) to salt walls, resulting in compartmentalized accumulation of strata whereby neighbouring mini‐basins record significant variations in sedimentary style at the same stratigraphic level. Despite the complexities created by halokinetic controls, the signature of climate‐driven sediment delivery can be deciphered from the preserved succession by comparison with the stratigraphic expression of part of the system that accumulated beyond the influence of halokinesis, and this approach can be used to demonstrate regional variations in climate‐controlled styles of sediment delivery.